Multitafsir Materi Sastra pada Ujian Nasional: Studi Kasus di SMAN 8 Denpasar - I Gusti Ketut Tribana, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This article gives an overview to the subject teachers ofIndonesian language and literature on many questionsregarding literary multiple interpretations. Also todetermine the effect of the questions about literature thatmultiple interpretations of the results of the NationalExamination (UN). It also contributes ideas for discussionfor teachers to better act, especially in answering thequestions of literary material in the National Exam (UN)senior high school in Bali and Indonesia.
Keywords: multiple interpretations; literature appreciation; national exam